A philosophical exploration of democratic participation in school governance in selected South African black schools in the Eastern Cape Province - Mabovula, Nonceba Nolundi (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Education Policy Studies))--Stellenbosch University, 2008.